1999
DOI: 10.1103/physrevb.59.5561
|View full text |Cite
|
Sign up to set email alerts
|

Origin of defect-related photoluminescence bands in doped and nominally undoped GaN

Abstract: The efficient room-temperature photoluminescence bands of wurtzite GaN, which are peaked in the red (1.8 eV), the yellow (2.2 eV), and the blue (2.8 eV) spectral range, have been studied as a function of doping (species and concentration) and excitation power density (PD). It is shown that the yellow and the blue band are induced by Si and Mg doping, respectively, while codoping with Si and Mg generates the red band. At high-doping levels, the yellow and the blue band reveal strong peak shifts to higher energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
184
3
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(203 citation statements)
references
References 20 publications
15
184
3
1
Order By: Relevance
“…The donorlike discrete state at E D = E C − 0.37 eV, which is probably related to the N-vacancy defect, 30,31 and the acceptorlike state at E A = E V + 1.0 eV, which is related to the Ga vacancy, 32,33 were assumed ͓Fig. 3͑a͔͒.…”
Section: ͑6͒mentioning
confidence: 99%
“…The donorlike discrete state at E D = E C − 0.37 eV, which is probably related to the N-vacancy defect, 30,31 and the acceptorlike state at E A = E V + 1.0 eV, which is related to the Ga vacancy, 32,33 were assumed ͓Fig. 3͑a͔͒.…”
Section: ͑6͒mentioning
confidence: 99%
“…Recently the YL in GaN has been found to exhibit a "blue-shift" with excitation intensity [10]. These and other experiments have suggested that YL is due to recombination between spatially separated donors and acceptors.…”
Section: Lbnl-44298mentioning
confidence: 95%
“…This is shown in Figure 2 The selectively-excited YL differs markedly from the E i > E g excited YL in its temperature dependence. One distinctive feature of the E i > E g YL noted in previous publications has been its lack of a dependence on temperature [10,18]. Figure 3 shows the selectively-excited YL spectra (E i = 2.471 eV) of a bulk sample measured for several temperatures (T) plotted on the same intensity scale.…”
Section: Lbnl-44298mentioning
confidence: 99%
See 1 more Smart Citation
“…The diagram is similar to those in Refs. [1] and [3], except that the difference in the energies of the EM and deeper donor states in our case needs to be much smaller than the 250 meV proposed in the former reference (this is since, in our case, the emission bands involving either the EM and or the deeper donors both lead to red emission). If we take the MM1 center to be Ga vacancy-related center, the scheme of Fig.…”
mentioning
confidence: 92%